MIL-53 (Fe) derived magnetic porous carbon as a robust adsorbent for the removal of phenolic compounds under the optimized conditions - Tran, Thuan Van; Cao, Vu Dai; Nguyen, Vinh Huu; Hoang, Bich Ngoc; Vo, Dai-Viet N.; Nguyen, Trinh Duy; Bach, Long Giang (Elsevier Ltd, 2020)
The presence of phenolic compounds in aquatic environment, derived from industrial, domestic or agricultural processes adversely affects the human and animals. This study in aimed at the new and effectiveness of an adsorbent, magnetic porous carbon (MPC), for the removal of phenolic compounds including phenol and 4- nitrophenol from aquatic environment. MPC was synthesized from the metal-organic framework MIL-53 (Fe) via the direct pyrolysis at 600 °C. The MPC structure was characterized by several physical techniques and used for the adsorption experiments. To find the best conditions for the removal of phenol and 4-nitrophenol, we empirically investigated the effects of three variables (initial concentration, dosage and pH) on the removal efficiency using the response surface methodology (RSM). Under the RSM-based optimized conditions, up to 83% phenol was removed at the concentration of 16 mg/L, dosage of 0.7, and pH of 6.6, while the figure for 4- nitrophenol was 97%, at concentration of 26.0 mg/L, dosage of 0.75 g/L, and pH of 5.6. In addition, the nonlinear adsorption kinetics and isotherms were employed to interpret the mechanism and calculate the constants of adsorption rate. The uptake results suggested that the adsorption process was controlled by the chemisorption and the monolayer adsorption. The MPC exhibited the remarkable maximum adsorption capacities, which is 4 times (for phenol) and 5 times (for 4-nitrophenol) higher than those exhibited by origin MIL-53 (Fe). Plausible adsorption mechanisms were explained through dipole-dipole H-bonding, π–π interaction and electrostatic attraction. Because of high capacity, effortless performance and good reusability, the MIL-53 (Fe) derived porous carbon can be a promising material for phenolic species remediation in water.